Statutory procedure and planning machinery for urban development in Sarawak / Mohammad Yusup - Yusup, Mohammad (2013)
This study is conducted to analyse the planning system in Sarawak within the context of overall planning components that govern the urban development in Sarawak.Weaknesses in the legal framework, planning administration, development plans as well as the development control system hindered the development process in Sarawak.The scopes of the study include the legal provision that shapes the planning system in Sarawak, the planning administrative system that governs the development process,the development plan instruments that used as guidance for current and future development and the development control machinery that facilitates the development process in Sarawak. Part X of Sarawak Land Code 1958 (Cap. 81) is used as the main reference in the planning system since the amendment made in 1997. According to the analyses ,the Part X of Sarawak Land Code 1958 (Cap. 81) is incapable to guide the whole development process in Sarawak due to incomprehensiveness of provision related to the urban planning. Analyses show that the centralisation of power by the State Planning Authority has caused single-tier planning administration structure in Sarawak. As a consequence of incomprehensiveness of provision with regards to the development plan system in Part X of the Sarawak Land Code 1958 (Cap. 81), the development plan in Sarawak is prepared in piecemeal and ad-hoc method which causes a lot of non-statutory planning and development process in Sarawak.Inefficiency in granting planning approval is due to the weaknesses in decision making process that include incomprehensive procedure of preparation of the development plans as well as the centralisation of power by the State Planning Authority. It is suggested that to solve the issues and problems that prevail in the planning system in Sarawak, independent and comprehensive planning enactment is indeed needed for Sarawak in order to achieve more systematic and comprehensive town planning system.